COVID-19 and Oral Fluids - Gaudin, Alexis; Badran, Zahi; Chevalier, Valérie; Aubeux, Davy; Prud'homme, Tony; Amador del Valle, Gilles; Cloitre, Alexandra (Frontiers in Dental Medicine, 2020)
The coronavirus disease 2019 (COVID-19) is an acute infectious disease caused by infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) leading to a global infectious disease pandemic. Main transmission is done through saliva droplets, this points to the fact that Oral fluids (OF) that includes saliva and non-salivary elements, contain infective viral loads of the virus. SARS-Cov-2 can entry the cells thanks to receptor angiotensin-converting enzyme II (ACE2) and the action of an enzyme (furin) that cleaves the viral envelope and enhances the infection of the host cells. Although origin, mechanism, and dynamics of SARS-Cov-2 in OF still remains to be elucidated; its presence in OF is now established. Therefore, it is legitimate to think that OF may serve as diagnostic or monitoring tool for COVID-19 either alone, either in combination with other tests in addition to the clinical examination. Another consequence of presence of SARS-Cov-2 in OF is the management of the infectious risk for dental practice. There is an urgent need to inform the dental community and also to ensure measures to protect dentists and dental staff from the new SARS-Cov-2. This comprehensive review related to COVID-19 and oral depicts the roles of OF in transmission dynamics of SARS-CoV-2, highlights the advantages of using OF as a diagnostic tool and focuses on the management of risk transmission related to OF in dental practice.